2012
DOI: 10.17221/278/2010-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of antilisterial bacteriocin-like substance produced by Enterococcus mundtii

Abstract: Solichová K., Složilová I., Jebavá I., Uhrová B., Plocková M. (2012): Characterisation of antilisterial bacteriocin-like substance produced by Enterococcus mundtii. Czech J. Food Sci., 30: 89-97.The antilisterial activity of e. mundtii 1282 strain and its cell-free neutralised supernatant was observed against five persistent l. monocytogenes strains using the agar spot method. The enterococcal metabolite was consequently characterised as a proteinaceous substance -the bacteriocin-like substance, which was heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Ent. mundtii CCM 1282, previously confirmed as a producer of thermostable enterocin-like substance (ELS) (Solichová et al 2012), showed the greatest antilisterial effect at all, namely against the five tested L. monocytogenes isolates . In the present study, the thermostability of ELS was confirmed by significant antilisterial activity caused by heated CFNS of Ent.…”
Section: Resultsmentioning
confidence: 95%
“…Ent. mundtii CCM 1282, previously confirmed as a producer of thermostable enterocin-like substance (ELS) (Solichová et al 2012), showed the greatest antilisterial effect at all, namely against the five tested L. monocytogenes isolates . In the present study, the thermostability of ELS was confirmed by significant antilisterial activity caused by heated CFNS of Ent.…”
Section: Resultsmentioning
confidence: 95%
“…BLIS BL4 was found active and stable over a wide range of pH from 2 to 9 ( Figure 1). Solichová et al, (2012) characterized an anti-Listeria bacteriocin-like substance produced by E. mundtii. This bacteriocin-like substance is heat-stable to 100 °C at 30 min; it is also stable in a wide range of pH value 2-10 ( Solichová et al, 2012).…”
Section: Blis Characterizationmentioning
confidence: 99%
“…Solichová et al, (2012) characterized an anti-Listeria bacteriocin-like substance produced by E. mundtii. This bacteriocin-like substance is heat-stable to 100 °C at 30 min; it is also stable in a wide range of pH value 2-10 ( Solichová et al, 2012). In another study, partially purified bacteriocin produced by E. faecium 130 isolated from mozzarella cheese was stable at pH ranging from 2 to 10 with no loss of activity after heating at 100 °C for 15 min (Tulini et al, 2011).…”
Section: Blis Characterizationmentioning
confidence: 99%